Code Team Training: Demonstrating Adherence to AHA Guidelines During Pediatric Code Blue Activations. Issue 12 (December 2021) - Stewart, Claire; Shoemaker, Jamie; Keller-Smith, Rachel; Edmunds, Katherine; Davis, Andrew; Tegtmeyer, Ken
Abstract : Objective: Pediatric code blue activations are infrequent events with a high mortality rate despite the best effort of code teams. The best method for training these code teams is debatable; however, it is clear that training is needed to assure adherence to American Heart Association (AHA) Resuscitation Guidelines and to prevent the decay that invariably occurs after Pediatric Advanced Life Support training. The objectives of this project were to train a multidisciplinary, multidepartmental code team and to measure this team's adherence to AHA guidelines during code simulation. Methods: Multidisciplinary code team training sessions were held using high-fidelity, in situ simulation. Sessions were held several times per month. Each session was filmed and reviewed for adherence to 5 AHA guidelines: chest compression rate, ventilation rate, chest compression fraction, use of a backboard, and use of a team leader. After the first study period, modifications were made to the code team including implementation of just-in-time training and alteration of the compression team. Results: Thirty-eight sessions were completed, with 31 eligible for video analysis. During the first study period, 1 session adhered to all AHA guidelines. During the second study period, after alteration of the code team and implementation of just-in-time training, no sessions adhered to all AHA guidelines; however, there was an improvement in percentage of sessions adhering to ventilation rate and chest compression rate and an improvement in median ventilation rate. Conclusions: We present a method for training a large code team drawn from multiple hospital departments and a method of assessing code team performance. Despite subjective improvement in code team positioning, communication, and role completion and some improvement in ventilation rate and chest compression rate, we failed to consistently demonstrate improvement in adherence to all guidelines.